Physical Activity Patterns in Older Men. (1st March 2015) - Bredland, Ebba Langum; Magnus, Eva; Vik, Kjersti
ABSTRACT: Introduction: There is mounting evidence to support the benefits of physical activity for older adults. Physical inactivity has become a growing challenge. Experience shows that older men participate less in community exercise programs; thus, there is a growing need to encourage active living. Aim: The aim of this study was to describe men's physical activity patterns in everyday routines. Methods: A time-geographic diary gathered data on activities during the day. Codes for metabolic equivalents (METS) were calculated by using diary data above 3 METS, moderate physical activity. Nine retired men were included in the study and wrote diaries for seven consecutive days. Results: The main result was that some of the men that did not formally exercise as recommended expended equal or a larger METS in daily activities. Conclusions: The participants demonstrated ways of obtaining the recommended physical activity quotient by performing physical activities during their daily routine. These findings can have implications for clinicians who encourage active living in senior men and for the development of new physical activity programs.